THE CONCEPTUAL FIELD OF LIFE, FATE AND HOMELAND IN ENGLISH AND UZBEK LITERARY TEXTS - Mamatqulova Xolida Axtamovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the conceptual field of life, fate, and homeland in English and Uzbek literary texts. It argues that these concepts create a semantic and emotional framework through which characters understand themselves, society, and moral responsibility. The research relies on cognitive and comparative approaches and uses Mamatkulova’s interpretation of universal concepts as a theoretical foundation. The article shows that English texts often emphasize individual destiny and social self-definition, whereas Uzbek texts frequently connect the same concepts with collective memory, family, national belonging, and spiritual endurance.